A formação de professores de surdos para a EJA: Uberlândia de 1990 à 2005 - Duarte, Kleyver Tavares (2022)
This research is a part of the line of History and Historiography of Education in the Graduate Program in Education at the Federal University of Uberlândia. The theme of this study is the training of teachers of Youth and Adult Education (EJA) who worked with the deaf. Thus, the objective of this study was to understand if there was and how was the training of teachers who worked with deaf students in the EJA modality from 1990 to 2005 in Uberlândia. The time frame had its starting point at the year of 1990, considering that this year the Alternative Education project began, which rescued young and deaf adults who were out of school because they did not find training after the 4th grade of the former 1st grade that met their needs, or because they dropped out before completing that series. This project started the structuring of Special Education in the municipal network of Uberlândia, which until then was non-existent. As the final period, the year 2005 was defined, due to the enactment of Decree no. 5,626 on December 22, 2005, which regulates Law no. 10,436, of April 24, 2002, which provides for the Brazilian Sign Language - "Libras", causing changes by instituting Libras as a mandatory subject in teacher training courses. Our hypothesis is that there was an educational proposal for deaf students in the researched period, but not a teacher training project that would meet all the needs of these deaf subjects. The methodology for carrying out this work was structured from the theoretical contribution in micro-history, having as research methodology the Oral History and gestural-visual, that is, a derivation of the Oral History that takes into account the specificities of the deaf researcher. As a result, we verified that the Education of Deaf Youth and Adults found space in the municipal education network of Uberlândia at first within the Alternative Teaching project that later, in 1996, came to constitute the Legal Basic Program for Alternative Education. It was from the development of this project that the first training of sign language teachers, interpreters and instructors took place, as well as other professional advisors, coordinators, supervisors, directors who came to work with deaf students both in regular education and in EJA and in special education. With the construction and execution of the Alternative Teaching Project, Uberlândia became a national reference in the area of Special Education and, especially in the area of deaf education, receiving awards and having a guaranteed place among the thirteen specialists in the country who were invited to participate in the elaboration of the bill that created the Brazilian sign language (Law nº.10.436/2002). Uberlândia was represented by teacher Mirlene Ferreira Macedo Damázio who was the creator and coordinator of the Alternative Teaching Project. However, around 1997, the place of EJA for the Deaf became part of the Illiteracy Eradication Program – PMEA and at this moment the training for professionals who worked with the deaf was modified. In this sense, we see that the importance given to the EJA modality is generally relegated to a secondary space in government actions and the same happened with the EJA for the deaf, which continued to exist, but without the same protagonism. The thesis defended here is that there was a well-structured teacher training to work with the Deaf in the education of Youth and Adults. Even though the proposal was not created to offer specific training for this purpose, as the intention was to carry out training aimed at special education as a whole, at first it had content aimed at the area of deafness and the students attended were the EJA deaf people. Keywords: Teacher Training; Deaf Education; Youth and Adult Education, Alternative Education.